Safety of withdrawal of pharmacological treatment after recovery from HER2 therapy-related cardiac dysfunction: the HER-SAFE trial - B Dowsing; H-M Dehbi; M S Andres; R Chung; A Oashou; J M Wilson; I Hussein; B Meredith; I Pierce; S Ahmed; J Pedra; O Worn; et al. (European Heart Journal, 2026)
Abstract Background Heart failure therapy (HFT) is routinely continued in breast cancer survivors after recovery from anti-HER2 cancer therapy-related cardiac dysfunction (CTRCD), despite limited evidence. HER-SAFE is the first randomised trial to assess HFT withdrawal in this population. Methods In this open-label, multicentre, randomised controlled trial, breast cancer survivors with recovered anti-HER2 CTRCD (asymptomatic, left ventricular ejection fraction [LVEF] ≥50%, normalised biomarkers) were randomised to HFT withdrawal or continuation. Antecedent CTRCD was mild (relative global longitudinal strain [GLS] decline >15%, LVEF ≥50%), moderate (LVEF fall >10% to <50%), or severe (LVEF <40%). The primary endpoint was a moderate or severe CTRCD event over 12 months analysed by intention to treat; secondary endpoints included serial cardiac function, biomarkers, and quality of life. Results Between July 2023 and June 2025, 90 patients were randomised (all female; median age 50 years [IQR 43–59]; median 17.3 months [IQR 7.7–33.2] since CTRCD recovery; HFT predominantly renin–angiotensin system inhibitors [98%] and beta-blockers [88%]) - 46 randomised to HFT withdrawal (1 lost to follow-up) and 44 to continuation. The primary endpoint occurred in 1 of 45 with withdrawal (moderate asymptomatic CTRCD) versus 0 of 44 with continuation (between-group difference 2.2pp; 90% CI upper limit 9.4pp). No cardiovascular deaths, heart failure hospitalisations or symptomatic CTRCD occurred. Cardiac magnetic resonance-derived LVEF remained stable in both arms at 12 months (between-group difference −0.8% [−2.0 to +0.4], p=0.21). Conclusions Among breast cancer survivors with recovered anti-HER2 CTRCD, HFT withdrawal was not associated with symptomatic events or significant between-group difference in LVEF at 12-months.